Silver Sulfadiazine Nanosystems for Burn Therapy - Venkataraman, Meenakshi (Springer US, 2012)
The objective of the present study was to formulate stable silver sulfadiazine (SSD) nanosuspensions and nanogels suitable for topical delivery with a view to increase bactericidal activity in burn therapy. SSD nanosuspensions were formulated using the microprecipitation–high-pressure homogenization technique. An optimized microsuspension of 0.5% SSD formulated with 6% Cremophor EL and 4% Lauroglycol 90 was subjected to 30 cycles of 1,000-bar pressure to give a nanosuspension with an average particle size of 367.85 nm. Transmission electron microscopy studies revealed that ovoid- to rectangular-shaped SSD particles were present as clusters. It was evident through X-ray diffraction studies that SSD was present in amorphous state both in microprecipitate and in nanosuspension. SSD (0.5%) nanogels were prepared using 1% Carbopol 974 P for topical delivery of nanosized SSD. In vitro release studies demonstrated that SSD release was faster from solutions and nanosuspensions compared to gel formulation owing to the influence of the gel matrix on SSD release. The bacterial inhibitory efficiency of SSD nanosuspension was as good as that of SSD solution against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. In vivo studies revealed that a nanogel containing 0.5% SSD was more effective in wound healing compared to 0.5% and 1% marketed cream.